Aplikasi Web Pemasaran Produk Makanan UMKM Dengan Fitur Pencarian Menggunakan Algoritma Boyer-Moore (Studi Kasus: UMKM Ombe Baru) - Rosita, Selvia (Journal of Computer Science and Information Technology, 2025)
The development of information technology provides great opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand the reach of their product marketing through digital media. However, many MSMEs still do not have an effective digital platform to market their products independently. This study aims to design and build a web application for marketing MSME food products with a search feature based on the Boyer-Moore algorithm, which can speed up the product search process and increase system efficiency. The system development method used is the Waterfall model, including the stages of needs analysis, design, implementation, testing, and maintenance. The application is built using HTML5, CSS3, JavaScript, PHP, and MySQL technologies, with the Boyer-Moore algorithm implemented in the search feature to speed up keyword matching. The test results show that the application runs well, is responsive, and is able to display search results quickly, especially when the amount of product data increases. Performance testing shows that the Boyer-Moore algorithm has a faster response time than conventional search methods. This application is expected to be a practical and efficient digital solution in helping MSMEs market food products independently and competitively in the digital era.